The Relationship Between Spiritual Intelligence and Burnout Among Mazandaran Medical School Residents During COVID-19 Disease Outbreak 2021-2022 - parastoo Jamallivani; mansoor ranjbar; mohammadreza Andarvazh; siavash Moradi (Babol University of Medical Sciences, 2023)
Background and Objective: Job burnout is one of the challenges of the health system and medical residents are among the most important pillars of service delivery, especially in epidemic conditions, and spiritual intelligence can be proposed as a way to relieve job burnout. The purpose of this study is to investigate the correlation between spiritual intelligence and job burnout in clinical teaching residents of Mazandaran University of Medical Sciences during the COVID-19 pandemic. Methods: This study is a questionnaire-based survey (cross-sectional study) that was conducted in 1400 with the participation of 36 residents from 3 educational groups of Mazandaran University of Medical Sciences. Maslach job burnout and King spiritual intelligence questionnaires were used for primary data collection and correlation analysis was done by calculating Pearson's coefficient (r) and statistical description and analysis was done using IBM SPSS version 25 software. Findings: The average burden of job burnout was 84.44 and the average burden of spiritual intelligence was 47.69. The production of personal meaning had a direct and significant correlation with job burnout, which was also observed in infectious residents. In emergency medicine residents; Job burnout has had a direct and significant correlation with spiritual intelligence and the subscales of critical existential thinking and the production of personal meaning and transcendental consciousness. Conclusion: According to the findings of the research, there is a need for more studies to examine the correlation between spiritual intelligence and burnout.